Dual-wavelength polarimetric glucose sensing in the presence of birefringence and motion artifact using anterior chamber of the eye phantoms - Malik, Bilal H. (Society of Photo-Optical Instrumentation Engineers, 2013)
Noninvasive glucose monitoring is being investigated as a tool for effectively managing diabetes mellitus. Optical polarimetry has emerged as one such method, which can potentially be used to ascertain blood glucose levels by measuring the aqueous humor glucose levels in the anterior chamber of the eye. The key limitation for realizing this technique is the presence of sample noise due to corneal birefringence, which in the presence of motion artifact can confound the glucose signature in the aqueous humor of the eye. We present the development and characterization of a real-time, closed-loop, dual-wavelength polarimetric system for glucose monitoring using both a custom-built plastic eye phantom (in vitro) and isolated rabbit corneas (ex vivo) mounted in an artificial anterior chamber. The results show that the system can account for these noise sources and can monitor physiologic glucose levels accurately for a limited range of motion-induced birefringence. Using the dual-wavelength system in vitro and ex vivo, standard errors were [Formula: see text] and [Formula: see text] , respectively, in the presence of birefringence with motion. The results indicate that although dual-wavelength polarimetry has a limited range of compensation for motion-induced birefringence, when aligned correctly, it can minimize the effect of time-varying corneal birefringence for a range of motion larger than what has been reported in vivo.